On the General Dedekind Sums and Two-Term Exponential Sums - Junli Zhang; Wenpeng Zhang (The Scientific World Journal)
We use the analytic methods and the properties of Gauss sums to study the computational problem of one kind hybrid mean value involving the general Dedekind sums and the two-term exponential sums, and give an interesting computational formula for it.